EVALUATION OF EFFICACY OF MANAGEMENT PROTOCOL IN ALLERGIC RHINITIS - Shah, Shahid Ali; Sajid, Tahira; Asif, Muhammad; Khan, Farida; Haroon, Tahir; Malik, Sohail; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Allergic rhinitis represents a global health issue affecting between 10% to 25% of the world population, with increasing prevalence, resulting in a significant impact on quality of life, multiple comorbidities and the considerable socio-economic burden. Majority of the patients are younger than 30 years and it may be inherited. Symptoms typically occur as a result of exposure to dust, dander or certain seasonal pollen. Lack of standardized management protocol is one of the major factors responsible for poor control of this condition. This study was designed to evaluate the patients suffering with allergic rhinitis and manage them with a protocol based on the pathogenesis of the condition. Method: This prospective study was conducted in the Department of Ear, Nose & Throat and Head & Neck Surgery, Ayub Teaching Hospital, Abbottabad, over a period of two years (2005 - 2006), to assess the efficacy of a standard protocol of treatment developed and followed in the department. 1167 patients, clinically diagnosed as suffering with allergic rhinitis, were evaluated and managed. Age ranged from 08 months to 64 years. All the patients were prescribed medical treatment, divided into initial phase of 10 days to two weeks duration followed by a maintenance phase, and a regular follow-up schedule was maintained upto two years. Results: 634 (54.32%) patients were male and 533 (45.67%) were female. Age ranged from 08 months to 64 years, 85% being between 05 and 45 years. 91% of patients had symptom duration of 06 months to 03 years. 96% of the patients were getting treated on as required basis, whereas 98% had no educational sessions with the treating doctor, especially regarding preventive measures. Typical presentation in most of the patients was nasal obstruction, runny & itchy nose, post nasal drip and bouts of sneezing. 90.57% patients reported improvement in symptoms. 53.21% patients had a relapse of symptoms at some stage during the study period. 37.53% patients had surgery done for associated pathologies, mostly a DNS. Compliance regarding medication was more than 90% in the initial phase of treatment that dropped to 50% in the maintenance phase. 93% of the patients tolerated the treatment well. Conclusion: Allergic rhinitis is a growing problem worldwide. Optimal treatment protocol is still lacking especially in the developing countries. Patient’s education on avoidance of allergens must be stressed. Associated problems that may need surgical treatment. Regular follow-up must be ensured to monitor the progress of treatment as well as to identify patients who might be candidates for immunotherapy. Newer modalities of treatment need to be further explored. A team approach is mandatory in the presence of symptoms related to lower respiratory tract. Key words : Allergic rhinitis; Treatment; Antihistamine; Intranasal corticosteroid; Surgery